The golden compass - Pullman, Philip, 1946- (New York : Ballantine Books, 1997)
Accompanied by her daemon, Lyra Belacqua sets out to prevent her best friend and other kidnapped children from becoming the subject of gruesome experiments in the Far North.
"A Del Rey book."
Originally published as: Northern lights.
Wilson's Senior High School.
Wilson's Junior High School.
Notable/Best Books (A.L.A.)
6.7
Keywords: Missing persons -- Experiments -- Juvenile fiction; Kidnapping -- Juvenile fiction; Arctic regions -- Juvenile fiction; Fantasy fiction